A design of encapsulated - Balloon type antenna for microwave therapeutic system by using finite element method - Phasukkit, P.; Tungjitkusolmun, S.; Jundang, S.; Sanpanich, A. (My University, 2014)
This research proposes a design of a novel microwave applicator which encapsulated in fluid reservoir for a thermal therapy. Heat generated from microwave energy is applied to cure or to reshape a hollow-tubing shape organ or misshape organ from occlusion or narrowing such as tracheal and benign prostatic hyperplasia. This promising technique provides a shorter treatment time and minimal invasive maneuver. We apply a coaxial microwave antenna which inserted into a small balloon reservoir filling with normal saline. The antenna is designed by using a finite element method (FEM). The characteristic of this proposed applicator is able to transfer effectively a heating from antenna to saline fluid in a silicone balloon. Our dominant advantage is the living tissue will not be severely burned due to directly contact with microwave antenna. Microwave energy of 2.45 GHz frequency in this simulation is trialed at 30 Watts while a total treatment time is 10 minutes by a pulsation control waveform as 1:10 ratio. A temperature distribution in our balloon is constant spreadly and steadily at 60-70 degree of Celsius during all treatment process which is a prominent point significantly of using a heating from balloon instead of a conventional antenna.
Keywords: coaxial opened-slot antenna; finite element analysis; microwave balloon treatment